AUTOMOBILE INJURIES IN ANDIJAN REGION - Siddikov Kutbiddin Marufjonovich (Лучшие интеллектуальные исследования, 2024)
Abstract: Specific aspects of auto injuries in 2023 are given according to the type of traffic participants, age, gender, and type of injuries.